Unpacking Mechanisms in Climate Resilient Agriculture Interventions. Issue 167 (6th October 2020) - Barrett, Sam; D'Errico, Stefano; Anderson, Simon; Nebsu, Bayu
Abstract: The investigation of causal mechanisms has the capacity to provide donors and implementing institutions with a greater understanding of people's reasoning and reactions as they work with interventions. This chapter contributes to the literature by identifying behavioral mechanisms generated through engagement with climate‐resilient agriculture interventions within a larger livelihood project in Ethiopia. It works through the steps that enabled the study to unpack the black box between the climate‐smart interventions and the outcome of crop production. The first step was a matching‐based sampling design, following households over 3 years with six biannual surveys, and setting up a quasi‐experimental evaluation setting. The second step used the data generated from the surveys in difference‐in‐difference models to assess the impact of the intervention on crop production. Third, to gain insight into the mechanisms at work, Focus Group Discussions (FGD) were conducted with smallholder farmer project beneficiaries. The FGDs revealed what the beneficiaries themselves considered the key mechanisms generated from the intervention, thus forming the bridge between the interventions and outcome. The result was an evaluation design enabling deeper insight into attribution claims. The findings offered novel insights for policymakers about how the climate‐resilient interventions worked for the people themselves and shedding light on the inner workings of the climate‐smart technologies. Finally, they provided key stakeholders (commissioning agency and implementing organizations) with a powerful means by which to learn about the last project, so to better plan for the next iteration and improve the climate resilience of smallholder farmers.